Hubungan Antara Mutu Jasa Pelayanan Kesehatan Dengan Kepuasan Pasien Rawat Jalan Di Puskesmas Sail Kota Pekanbaru - Arnila Melina (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2024)
Health services in Indonesia are one of the many components of the health system that have direct contact with the community. The quality of health services is so important because it makes it easier for people to carry out health checks. Patient satisfaction can also be obtained from the quality of health services received from the health center. The quality of services provided to service recipients can affect their satisfaction with the health services provided by service providers. This study aimed to determine the relationship between each dimension of the quality of health services and patient satisfaction at the Sail Health Center in Pekanbaru City. This research is included in quantitative research with an analytic survey and cross-sectional study approach. The number of samples in this study was 95 outpatients at the Sail Health Center in Pekanbaru City. According to the statistical results of the Fisher's Exact test, there is a relationship between the quality of health services and outpatient satisfaction at the Sail Health Center, Pekanbaru City. Suggestions that can be given are the allocation of health workers by duties and responsibilities, such as the number of health workers by duties and responsibilities and the need for Puskesmas Sail to conduct regular patient satisfaction surveys to evaluate the quality of services at Puskesmas Sail.